Lakon Panji; Stroytelling Berbasis Cerita Rakyat untuk Mendukung Terbentuknya Profil Pelajar Pancasila Peserta Didik (Prosiding Konseling Kearifan Nusantara (KKN), 2022)
Guidance and counseling in merdeka belajar curriculum has the goal, its for accommodating the needs of students and helping them to be able understand aboute their talents, interests, and potential and have a strog character for their future. In its service, BK has a strategy which is includes the basic components of BK. One ofe the techniques in one ofe the basic components of BK is storytelling based on the folklore lakon Panji. Storytelling can be used to convey the oral or character of story to students. Lakon Panji is story of life of Raden Panji Asmarabangun for seeking knowledge and insight to provide life provisions. Lakon Panji can be developed by the BK teacher and or counselor by inserting a Pancasila students profile character, as long as in story development and the addition of new characters, cannot be separated from the characters that must be in it